Jože Rajhman, življenje in delo - Krajnc-Vrečko, Fanika (Edinost in dialog, 2025)
This paper outlines the life of Jože Rajhman (1924-1998) with the most important milestones in his life that marked his work as a priest, theological professor and insightful thinker of a broad philological and spiritual format. Emphasis is placed on the presentation of his extended family and his father Joseph. He spent his childhood and adolescence in the turbulent pre-war period and his family's exile during the Second World War, where he encountered a cultural environment in Serbia that was entirely new to him. His first decision to study Slovenian and Romance studies soon turned into a decision to become a priest and to study theology, but he later returned to his first field of interest, philology. The many jobs he held in different cities, from Ljubljana, Celje, Marija Snežna to Maribor, were linked to the priestly profession, in which he came under scrutiny from the authorities and the long-lasting trials during his first decade of ministry. In addition to his priestly vocation, he later found the time and motivation to research Slovenian spiritual, cultural and literary history, which placed him among the leading experts on Slovenian Protestantism and its main protagonist, Primož Trubar. His published philological and theological works are already quite well researched, while his manuscript material offers opportunities for further research and evaluation. On the occasion of the centenary of his birth, he is remembered in the context of his modest life and rich activity, and this paper seeks to add to the existing knowledge of his life and work.
Keywords: biografija; biography; delo; extended family; Rajhman, Jože; sodni procesi; širša družina; trials; work